The diagnostic value of the combined application of blood lipid metabolism markers and interleukin-6 in osteoporosis and osteopenia - Liping Fan; Jiahao Chen; Chong Chen; Yongwei Zhang; Yeqing Yang; Zhe Chen (Lipids in Health and Disease)
Abstract Background This study aimed to analyse the relationship of the blood lipid profile and interleukin-6 (IL-6) with osteoporosis and osteopenia and to explore the predictive value of the combined application of these biomarkers in osteoporosis and osteopenia. Methods Data from 276 patients treated in the orthopaedics department were retrospectively analysed. Their general information was collected, and the relationships among the blood lipid profile, IL-6 with bone turnover markers, and bone mineral density (BMD) were analysed. Patients were categorized based on their T scores for intergroup comparisons. Finally, the diagnostic efficiency of lipid metabolism markers and IL-6 for osteoporosis and osteopenia was assessed using receiver operating characteristic (ROC) curves. Results (1) In both males and females, a negative relationship was observed between BMD and several biomarkers, including total cholesterol (TC), apolipoprotein B (ApoB), low-density lipoprotein cholesterol (LDL-C), free fatty acids (FFAs), and IL-6. Additionally, apolipoprotein A1 (ApoA1) was negatively correlated with BMD only in females, and the ApoA1/ApoB ratio was positively correlated with BMD only in males. (2) FFAs and IL-6 were positively correlated with β-CrossLaps peptide in males. However, for females, TC, ApoB, LDL-C, and IL-6 were negatively correlated with 25-hydroxyvitamin D. FFAs, IL-6, and age were negatively correlated with osteocalcin in males and females. (3) According to the T scores for the lumbar spine, the TC, ApoA1, ApoB, HDL-C, LDL-C, FFA, and IL-6 levels in the osteoporosis group and the TC, ApoB, LDL-C, and FFA levels in the osteopenia group were significantly greater than those in the normal bone mass group. Additionally, the osteoporosis group presented substantially higher levels of ApoA1, FFAs, and IL-6 than the osteopenia group. (4) IL-6 was positively correlated with FFAs, while a negative correlation was observed with TC, ApoA1, ApoB, HDL-C, and LDL-C. (5) The ROC curve revealed that the areas under the curve (AUCs) of TC, FFAs, IL-6, ApoA1, and the ApoA1/ApoB ratio for predicting osteoporosis or osteopenia were 0.634, 0.713, 0.670, 0.628, and 0.516, respectively, whereas the AUC of the combination of TC, FFAs, IL-6, and ApoA1 was 0.846, and the AUC of the combination of TC, FFAs, IL-6, and the ApoA1/ApoB ratio was 0.842. In the sex stratification analysis, in males, the AUCs of TC, FFAs, IL-6, and the ApoA1/ApoB ratio for the prediction of osteoporosis or osteopenia were 0.596, 0.688, 0.739, and 0.539, respectively. In contrast, the AUC of the combination of TC, FFAs, IL-6, and the ApoA1/ApoB ratio was 0.838. In females, the AUCs of TC, FFAs, IL-6, ApoA1, and the ApoA1/ApoB ratio for predicting osteoporosis or osteopenia were 0.620, 0.728, 0.653, 0.611, and 0.502, respectively, whereas the AUC of the combination of TC, FFAs, IL-6, and ApoA1 was 0.841, and the AUC of the combination of TC, FFAs, IL-6, and the ApoA1/ApoB ratio was 0.828. Conclusion The levels of TC, FFAs, IL-6, ApoA1, and ApoB could contribute to changes in bone metabolism, moreover, FFAs could induce an increase in IL-6 further aggravating bone mass loss and leading to osteoporosis. Based on the comparison of the AUC results, the combination of TC, FFAs, and IL-6 with ApoA1 or the ApoA1/ApoB ratio can better predict osteoporosis or osteopenia in patients, and the diagnostic efficiency is significantly better than that of any individual indicator. The regulation of blood lipid levels should become a new target for clinicians to treat osteoporosis and osteopenia.